Evaluation of Bacillus amyloliquefaciens in the control of Botrytis cinerea in Rosa sp. - Campués Cholca, Sandra Verónica (2023)
In the first two months of 2022, flower exports reached 197 million dollars, representing a 7% increase compared to the same period in 2021. To maintain this growth rate, it is important to efficiently control pathogens that threaten productivity, such as Botrytis cinerea, which causes significant crop loss in roses. Therefore, the objective of this research was to evaluate the effectiveness of Bacillus amyloliquefaciens in controlling B. cinerea in Rosa sp. A completely randomized design with four treatments and three replications was used to compare the frequency of application of B. amyloliquefaciens versus chemical management. Treatment application of B. amyloliquefaciens every 4 days (A2) maintained an incidence and severity percentage between 0 and 2%, while treatment A1 ranged between 10 and 14%. Regarding the variable vase life, treatment A2 achieved 83% of roses in good condition, while treatment A1 reached 63%. These results clearly demonstrate the effectiveness of using biological products.